The Family Approach for Scaling Out of Leaf Colour Chart Based Nitrogen Management in Rice - Rashid, M Harunur; Khan, MA Hossain; Alam, M Murshedul (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> In the traditional technology transfer process, the role of active participation of family members, immediate to household head, is not considered. Two sets of target audiences, lead farmers for the traditional method and family members for the family approach were trained to evaluate the expansion scenario of Leaf Colour Chart (LCC) based nitrogen management in rice. In the family approach (FA), young sons or brothers of the farmers helped in demonstrating the new technology and adoption by participating in the field activities directly. On the other hand, young daughters and wife helped in keeping the LCC in a safe place, reminded the farmers about the fertilizer rate and date for taking LCC readings and timely application of nitrogen following LCC use guidelines. On an average, each trained family shared knowledge on the technology with 6.2 neighbouring farmers whereas 2.03 farmers were informed by each lead farmer. The technology adoption was enhanced remarkably due to participation of family members. The higher rate of adoption of FA technology by the neighboring farmers compared to Lead Farmer Approach (LFA) proved its cost effectiveness. Key words: Leaf colour chart, rice, cost-effectiveness. DOI = 10.3329/jard.v5i1.1455 J Agric Rural Dev 5(1&2), 36-42, June 2007